What Is the Structure of Time? A Study on Time Perspective in the United States, Poland, and Nigeria - Sobol-Kwapińska, Małgorzata; Jankowski, Tomasz; Przepiorka, Aneta; Oinyshi, Ike; Sorokowski, Piotr; Zimbardo, Philip (Frontiers in Psychology, 2018)
The aim of this article was to analyse the fit of the model of time perspective, measured by the Zimbardo Time Perspective Inventory, to data collected in three countries: the USA (N = 283), Poland (N = 510), and Nigeria (N = 357). Confirmatory factor analyses, exploratory structural equation modelling, an expected parameter change and parallel analysis were used. The best-fitted model of time perspective was the one in the USA, and the least fitted model was the one in Nigeria. Possible sources of misspecifications in the model of time perspective were discussed. We also present an analysis of the fit of the four-factor model of time perspective. The four-factor model was very well fitted in the USA and in Poland. Results were discussed in the context of clock time and event time theory.